BS P04 Global Level of Harm experienced by Bariatric Surgeons for Bariatrics surgical interventions: An exploration of predictors. (7th December 2022) - Cheruvu, Chandra; Bangash, Ali Haider; Isik, Arda; Parmar, Chetan; Galanis, Michail; Yang, Wah; Herrera Kok, Johnn Henry; Bandyopadhyay, Samik Kumar; Di Maggio, Francesco; Atici, Semra Demirli; Abouelazayem, Mohamed; Viswanath, Yirupaiahgari K S
Abstract: Background: COVID-19 pandemic has taken the world by surprise with the depth and breadth of its effect on all walks of life, bariatric surgery being no exception. With the scientific literature hitherto unable to comment and ascertain the influence of the COVID-19 pandemic on bariatric surgery and the level of harm experienced by bariatric surgeons, we- TUGS 'Level of Harm' collaborative group- attempted to gauge the effect of the said pandemic on bariatrics surgery specifically vis a vis the level of harm experienced by bariatric surgeons due to the pandemic. Methods: A virtual questionnaire- developed on both: Google forms and Survey Monkey- was circulated via TUGS social media platforms to reach bariatric consultant surgeons, fellows and residents practising throughout the world in a bid to explore the influence of the COVID-19 pandemic on their surgical practice including but not limited to the annual surgical volume including re-do surgeries volume and postoperative complications. Moreover, they were also requested to categorise their respective level of harm vis a vis bariatric surgical interventions they undertake. After de-identification of the data, SPSS (V.26) was adopted to undergo statistical analysis. After exploring the dataset by descriptive analyses, the Chi-square test was applied to pursue the association of categorical variables with the reported level of harm. A double-sided p-value of less than 0.05 was considered statistically significant. Results: 16.8% of the respondents (21/125) indicated no harm vis a vis bariatrics surgery work whereas a comparative 18.4% of the respondents (23/125) reported moderate harm with significant worsening of symptoms. None of those who indicated less than 10% increase in surgery waitlisted patients being subjected to endoscopic interventions (0/14) reported Moderate Harm for bariatrics surgery work with significant worsening of symptoms whereas 1 in every 3 of those who indicated between 10% to 25% increase in surgery waitlisted patients being subjected to endoscopic interventions (5/15) reported such level of harm for bariatrics surgery work. (p < 0.001) Upon exhaustive sub-group analysis, it was uncovered that 33.6% of bariatrics surgical professionals perceived no harm (no evidence of change in clinical condition) during gastric band or related surgery work with only 4% perceiving Moderate Harm (significant worsening of symptoms/ comorbidities control/ minor increase in medications) for such surgical interventions. All of those who reported No harm for gastric band or related surgical work reported that Single anastomosis duodeno–ileal bypass (SADI-S) accounts for 10% of their practice whereas none of those who indicated that SADI-S accounts for more than 10% of their practice reported No harm for such surgical work. (p = 0.019) Conclusions: The global snapshot illustrates a trend of low harm vis a vis bariatrics surgery work in surgical professionals practising in the private sector with a lesser number of patients developing COVID-19 postoperatively and no postoperative COVID-19 related mortality. The patient being subjected to endoscopic intervention portends a higher level of harm for bariatrics surgical work- strict adherence to criteria and safety protocols being a logical inference. For gastric band and related surgery work, preoperative COVID-19 testing appears to be influenced by confounders in its effect on the surgeon's level of harm for the said interventions warranting further exploration. SADI-S, at a cut-off of 10%, exhibits strong interaction with the surgeon's level of harm for gastric band insertion and relation surgery work. Women surgical professionals came out to exhibit equivalent mental resilience and technical prowess at par with their male colleagues when it came to bariatrics surgical intervention.